Immunobiology of Acquired Resistance to Ticks - Karasuyama, Hajime; Miyake, Kensuke; Yoshikawa, Soichiro (Frontiers in Immunology, 2020)
Ticks are blood-sucking arthropods of great importance in the medical and veterinary fields worldwide. They are considered second only to mosquitos as vectors of pathogenic microorganisms that can cause serious infectious disorders, such as Lyme borreliosis and tick-borne encephalitis. Hard (Ixodid) ticks feed on host animals for several days and inject saliva together with pathogens to hosts during blood feeding. Some animal species can acquire resistance to blood-feeding by ticks after a single or repeated tick infestation, resulting in decreased weights and numbers of engorged ticks or the death of ticks in subsequent infestations. Importantly, this acquired tick resistance (ATR) can reduce the risk of pathogen transmission from pathogen-infected ticks to hosts. This is the basis for the development of tick antigen-targeted vaccines to forestall tick infestation and tick-borne diseases. Accumulation of basophils is detected in the tick re-infested skin lesion of animals showing ATR, and the ablation of basophils abolishes ATR in mice and guinea pigs, illustrating the critical role for basophils in the expression of ATR. In this review article, we provide a comprehensive overview of recent advances in our understanding of the cellular and molecular mechanisms responsible for the development and manifestation of ATR, with a particular focus on the role of basophils.